Designs with maximally different blocks and υ = 15,16 - Bluskov, Iliya (Utilitas Mathematica, 1996)
This work contains results on the existence and the parameters of designs with maximally different blocks (DMDB's) on 15 and 16 points. The observation that some DMDB's contain "genetic" information for many other DMDB's is used for most of the constructions. A variation on the greedy algorithm acting on the blocks of the design is also used in some cases.